Animal Hygiene Indexes in Relation to Big-Five Personality Traits of German Pig Farmers Evaluated by Self- and Other-Rating - Döring, Susanne; Geisthardt, Nicole; Freitag, Henrike; Kobusch, Iris; Boelhauve, Marc; Mergenthaler, Marcus (Frontiers in Veterinary Science, 2019)
Improving biosecurity in intensive livestock production has become an increasingly challenging task. Often, animal hygiene measures are implemented at lower levels than recommended. Therefore, veterinarians and farm advisors look for new approaches to improve their advisory process with farmers. In the current study it has been hypothesized that German pig farmers' big-five measured personality traits might correlate with farms` biosecurity level expressed by a ‘continuous animal hygiene index’ and a ‘technical animal hygiene index’. Hence, comprehen-sive data on the implementation of more than 100 hygiene measures were collected at farm level from a specific pilot sample of 42 pig farmers from a livestock intensive region in north-western Germany. In addition, big-five personality traits (BFI-S) were measured by self- and other-rating. Inter-rater reliabilities for personality traits indicated expected positive correlations apart from agreeableness (rS = -.101). Regarding the self-rating, neuroticism was valued lowest (x̅ = 3.88 ± 1.18) and conscientiousness highest (x̅ = 5.68 ± 0.70). The animal hygiene indexes re-vealed medium biosecurity levels on the participating farms. Piglet breeders had a significantly higher value for the ‘continuous animal hygiene index’ (x̅ = 63.00 ± 9.91 %). Personality traits conscientiousness and openness showed correlations with the continuous and the technical ani-mal hygiene index. Depending on the production systems as well as the rating perspectives cor-relations varied. For one of the personality traits playing a direct role in social interaction – ex-traversion – the advisory process might function as a mediating factor. The current results show that clustering of single hygiene measures into indexes in the evaluation of pig farms` biosecuri-ty level might have advantages. The preliminary results from this study should be validated in larger, more representative samples. Furthermore, structured and systematic consideration of personality traits of farmers adds an additional aspect to include individuality of farmers more systematically in complex advisory processes. Interaction of personality traits with characteris-tics of the advisory process should be further researched and should be included in a much broader socio-political understanding of what is involved in changing practices.